Students' Perception on the Implementation of Online Learning in English Speaking Skill - Krisyanti, Yaqilul; Taufiq, Wahyu (Jurnal Pendidikan Jarak Jauh, 2023)
Due to the Covid-19 pandemic, the government stipulated the PPKM agenda that limit the social interaction in public place, including school. Since then, the teaching and learning process was conducted through online learning. this research aims to know the students' perception toward the use of online learning in students’ speaking skills at Junior High School Al-Fattah Buduran Sidoarjo. In this research, the researcher focuses on the development of speaking skills in students through online learning during the pandemic. This research is a descriptive qualitative method by emphasizes a variety of approaches and takes an interpretive and naturalistic approach to its subject. Based on the research result, it was found that the implementation of online media for English speaking skill is considered less efficient for students since they are unable to practice their speaking ability with their teachers or their classmates. In addition, the most frequent obstacles faced by students in online learning is the poor signal and connection in their home or the teachers’ home that caused students experience the difficulties in understanding the lesson.